Characteristics of sports injuries and prevention strategies for Chinese basketball teams - Ye, R. B.; Zhang, M.; Du, W. L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of the study is to understand the incidence of common sports injuries in China`s high level basketball players and to investigate the relationship between injuries and training period, training load, and other correlative factors[1]. An additional goal was to use the information to establish an injury prevention system for basketball players with the aim of reducing the risk of injury in mens` women`s basketball teams for the Olympic Games in 2008. Methods Questionnaire surveys were used to collect data during the training period for elite basketball players from 2006-2007. Region of injury, characteristics of the injury, and causes of injury were analysed. Results The analysis indicated that injuries to the knee, ankle, waist, and fingers had the highest incidence rate; compared with non-elite basketball players, injuries of the ankle had a lower incidence rate. Injuries of the fingers were higher in the elite athletes. Conclusions China`s elite basketball players had their own unique injury patterns, and these patterns were closely related to different technical characteristics, different body parts and proper use of protective equipment. The occurrence of sports injuries can be reduced if proper injury prevention strategies are adopted.